2011
DOI: 10.1007/s10641-011-9910-3
|View full text |Cite
|
Sign up to set email alerts
|

Pre-spawning migration of adult Pacific lamprey, Entosphenus tridentatus, in the Willamette River, Oregon, U.S.A.

Abstract: We describe the migration distances and timing of the adult Pacific lamprey, Entosphenus tridentatus, in the Willamette River Basin (Oregon, U.S.A.). We conducted aerial surveys to track radiotagged fish upstream of a major waterfall and hydropower complex en route to spawning areas. We detected 24 out of the 43 fish that passed the waterfallhydropower complex. Of the detected fish, 17 were detected multiple times. Their maximum migration distance upstream in the mainstem Willamette approximated a normal distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 9 publications
2
20
0
Order By: Relevance
“…Our findings suggest actions that increase accessibility and improve habitat conditions could contribute to halting the ongoing decline of Pacific Lamprey, an immediate goal of recovery planning (CRITFC 2011). Migrating Pacific Lampreys are widely distributed in the Willamette River basin throughout accessible habitats (Clemens et al 2012a(Clemens et al , 2012b, and we documented spawning activity in all reaches that we surveyed. Our results indicated that Pacific Lampreys are capable of spawning in a wide diversity of stream sizes and underlying geologic types, provided there are no barriers to upstream migration.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…Our findings suggest actions that increase accessibility and improve habitat conditions could contribute to halting the ongoing decline of Pacific Lamprey, an immediate goal of recovery planning (CRITFC 2011). Migrating Pacific Lampreys are widely distributed in the Willamette River basin throughout accessible habitats (Clemens et al 2012a(Clemens et al , 2012b, and we documented spawning activity in all reaches that we surveyed. Our results indicated that Pacific Lampreys are capable of spawning in a wide diversity of stream sizes and underlying geologic types, provided there are no barriers to upstream migration.…”
supporting
confidence: 58%
“…Spawning surveys began in 2012 on Clear and Thomas creeks and the Marys River and comprised two survey segments in each stream (Table 1); the Marys River had contiguous survey segments and Clear and Thomas creeks had survey segments that were discrete spatially ( Figure 1). We had previously conducted larval lamprey surveys in these tributaries, and adult migration studies documented adult lamprey movement into smaller tributary subbasins of the Willamette River (Clemens et al 2012a(Clemens et al , 2012b. In 2013, we continued spawning surveys in the Marys River and Clear and Thomas creeks and included a single survey segment on each of the Calapooia and Luckiamute rivers (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found a strong relationship between water temperature and travel times through the fishway, consistent in both years, indicating that Pacific Lampreys moved faster through the fishway at higher temperatures (e.g., 0.4 d at 17°C) than at lower temperatures (e.g., 1.4 days at 12°C). Temperature appears to have important influences on lamprey upstream migration behavior (Keefer et al 2009;Binder et al 2010;Clemens et al 2012;Castro-Santos et al 2017). For example, the migratory activity of Sea Lamprey Petromyzon marinus increases with day-to-day increases in water temperature but decreases with declines in temperature .…”
Section: Discussionmentioning
confidence: 99%
“…Instead, temperature and flow appear to be the key triggers influencing timing of upstream migration. Change in temperature also appears to signal cessation of movement in preparation for overwintering by Pacific lamprey in the Columbia River basin (Robinson and Bayer 2005;Mesa et al 2010b;Clemens et al 2012). Temperature dictates fish distribution (e.g., Buisson et al 2008) and controls initiation and efficiency of movement (e.g., Jonsson 1991;Rodriguez-Ruiz and Granado-Lorencio 1992).…”
Section: Environmental Triggers Initiating Migratory Behaviormentioning
confidence: 99%